2012
DOI: 10.1063/1.4739778
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and transport properties of two-temperature SF6 plasmas

Abstract: This paper deals with thermodynamic and transport properties of SF 6 plasmas in a two-temperature model for both thermal equilibrium and non-equilibrium conditions. The species composition and thermodynamic properties are numerically determined using the two-temperature Saha equation and Guldberg-Waage equation according to deviation of van de Sanden et al. Transport properties including diffusion coefficient, viscosity, thermal conductivity, and electrical conductivity are calculated with most recent collisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 61 publications
(69 reference statements)
0
17
0
Order By: Relevance
“…Even the correct method of calculation of the species composition in the case when the electron and heavy-particle temperatures differ is still the subject of debate. [25][26][27][28] (2) Determination of the electron energy distribution function. The critical electric field is the field corresponding to a balance between the processes of electron generation and loss.…”
Section: Calculation Methods To Determine the Dielectric Propertiesmentioning
confidence: 99%
“…Even the correct method of calculation of the species composition in the case when the electron and heavy-particle temperatures differ is still the subject of debate. [25][26][27][28] (2) Determination of the electron energy distribution function. The critical electric field is the field corresponding to a balance between the processes of electron generation and loss.…”
Section: Calculation Methods To Determine the Dielectric Propertiesmentioning
confidence: 99%
“…Concerning the 2T thermodynamic properties, the expressions are accepted by the plasma community except for the specific heat which is either calculated as a unique coefficient or divided in two coefficients corresponding to the electron and the heavy contributions. For the 2T transport properties, several works were published [117][118][119][120][121][122] and used two approached: with coupling or without coupling between the electrons and the heavy particles. Ghorui 116 and Colombo 117 compared the two theories and concluded that Devoto's approach (without coupling) was adequate to determine the electrical conductivity, the viscosity and the thermal conductivity of a nonequilibrium plasma even if the diffusion coefficients used in the expressions were obtained by the Ramshaw's approach.…”
Section: Discussionmentioning
confidence: 99%
“…The species compositions of air and the air-organic vapor mixtures at different mixing ratios and pressures (0.1-10 atm) from gas temperature to 4000 K were obtained by minimizing the Gibbs free energy [8]. These species compositions were calculated under the assumption of local thermodynamic and chemical equilibrium.…”
Section: Species Composition Of the Hot Gas Mixturesmentioning
confidence: 99%